Effect of levels of intake on rumen fermentation, digestibility, methane emissions and behaviour - Moya D.; Newbold C.J. (Innovation for sustainability in sheep and goats, 2019)
The objective of this experiment was to examine the effect of differing levels of intake on rumen fermentation profile, nutrient digestibility, methane emissions, and feeding behaviour in sheep. Six Aberdale cross Texel ewes (90.2 ± 1.89 kg BW) fitted with rumen fistula were used in a duplicated 3×3 Latin Square with three 21-d experimental periods. Treatments comprised dried grass nuts fed to meet one (1M), 1.5 times (1.5M), or two times (2M) maintenance energy requirements (NRC, 2007). The average daily gain was greater in 2M than 1M ewes. The 1M ewes had a lower VFA concentration than 1.5M and 2M, and a greater aceticto-propionic ratio than 1.5M. The ammonia concentration was greater in 1.5M than in 2M ewes. Dry and organic matter digestibility per unit of metabolic weight were greater in 1M than 1.5M and 2M ewes. Emissions of methane per unit of DM intake were greater in 1M than 1.5M and 2M ewes. No differences were found in protozoa count, feeding behaviour or haematology. Results show that increased levels of intake have a measureable impact on diet fermentation and digestibility, reducing the acetate-to-propionate ratio, ammonia production, digestibility rate, and methane emissions. These changes could be attributed to the different nutrient fermentation pattern and the higher flow rate from the rumen to the lower digestive tract.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)